Expression of Quaking RNA-Binding Protein in the Adult and Developing Mouse Retina. - Takahiko Suiko; Kensuke Kobayashi; Kentaro Aono; Togo Kawashima; Kiyoshi Inoue; Li Ku; Yue Feng; Chieko Koike (PLoS ONE, 2016)
Quaking (QKI), which belongs to the STAR family of KH domain-containing RNA-binding proteins, functions in pre-mRNA splicing, microRNA regulation, and formation of circular RNA. QKI plays critical roles in myelinogenesis in the central and peripheral nervous systems and has been implicated neuron-glia fate decision in the brain; however, neither the expression nor function of QKI in the neural retina is known. Here we report the expression of QKI RNA-binding protein in the developing and mature mouse retina. QKI was strongly expressed by Müller glial cells in both the developing and adult retina. Intriguingly, during development, QKI was expressed in early differentiating neurons, such as the horizontal and amacrine cells, and subsequently in later differentiating bipolar cells, but not in photoreceptors. Neuronal expression was uniformly weak in the adult. Among QKI isoforms (5, 6, and 7), QKI-5 was the predominantly expressed isoform in the adult retina. To study the function of QKI in the mouse retina, we examined quakingviable(qkv) mice, which have a dysmyelination phenotype that results from deficiency of QKI expression and reduced numbers of mature oligodendrocytes. In homozygous qkv mutant mice (qkv/qkv), the optic nerve expression levels of QKI-6 and 7, but not QKI-5 were reduced. In the retina of the mutant homozygote, QKI-5 levels were unchanged, and QKI-6 and 7 levels, already low, were also unaffected. We conclude that QKI is expressed in developing and adult Müller glia. QKI is additionally expressed in progenitors and in differentiating neurons during retinal development, but expression weakened or diminished during maturation. Among QKI isoforms, we found that QKI-5 predominated in the adult mouse retina. Since Müller glial cells are thought to share properties with retinal progenitor cells, our data suggest that QKI may contribute to maintaining retinal progenitors prior to differentiation into neurons. On the other hand, the expression of QKI in different retinal neurons may suggest a role in neuronal cell type specific fate determination and maturation. The data raises the possibility that QKI may function in retinal cell fate determination and maturation in both glia and neurons.